Parametric Study Of Geogrid Reinforced Road Embankment Over Soft Soil - Betel Biru (ASTU, 2023)
All Roads, Whether They Are Built Above Or Below The Ground Surface, Use Naturally Occurring Soils And Rocks As The Basic Foundation And Construction Materials. The Construction Of Embankment Over Soft Soil Is Increasing Due To Lack Of Suitable Land For Infrastructure And Other Development. Embankment Foundation Containing Soft Grounds Is Often A Challenge For Geotechnical Engineers To Ensure Stability Depending On The Nature Of The Soil. Construction Of Pavement On Weak Or Soft Soil Is Highly Risky Because Such Soil Is Susceptible To Differential Settlements, Poor Shear Strength, And High Compressibility. Instability Problems Such As Lateral Deformations And Excessive Settlement Often Occur In Structural And Geotechnical Construction On Soft Soils. , Various Methods Exist To Improve Compressible Soils Commonly Applied On-Site Including Preloading, Lightweight Fill, Geosynthetic Reinforcement, Over-Excavation And Replacement, Vertical Drains, Rigid Piles, And Injection. Despite The Fact That Existing Methods May Mitigate Stability Problems, Selection Factors Need To Be Considered, Such As Sustainability, Cost, And Time Of Construction. Enhancing Density, Increasing Shear Strength, And Reducing Compressibility Can Help In Promoting Stability. Thus, The Present Study Is Aimed To Address These Issues By Developing A Model Of Geogrid Reinforced Road Embankment Over Soft Soil Under Traffic Load. Plaxis 2d Software Is Used For This Research In Conjunction With The Mohr-Coulomb Model, Which Is Adopted For The Subgrade Soil And Embankment And Linear Elastic Model For The Ac Pavement And Geogrid Reinforcement. Parametric Study On Side Slope, Axial Stiffness And Height Of Embankment Is Also Conducted In Order To Know Their Influence In Performance Of Embankment. The Modeling Has Shown That The Performance Of Geogrid Reinforced Road Embankment For Efficient Combination Is Side Slope Of 3h:1v, Tema-Xgrid-300(Ea 1600kn/M) For 1m Selected And Recommended As The Most Efficient Combination Of The Rest All. The Settlement Of The Reinforced Embankment Was Reduced By 33% And Lateral Displacement Reduced By 15% Of Unreinforced One. The Performance Of Geogrid Reinforced Road Embankment For 2m And 3m , Height With Respect To Settlement Efficient Combination Is Side Slope Of 1.5h:1v And Tema-Xgrid-300(Ea-1600kn/M) In Which Settlement Of The Reinforced Embankment Was Reduced By 30%And 25% Respectively Of Unreinforced One
Keywords: soft soil, Geogrid, PLAXIS 2D, Mohr-coulomb model